Meningkatkan Sistem E-Government di Indonesia: Perbandingan dengan Sistem NemID Denmark - Fauziah, Ulfah; Aziz Harahap, Ibrahim (Fakultas Hukum Universitas Islam Malang, 2024)
The Indonesian government provides public services through an e-government system carried out over the network websites, applications, or social media. This is done so that people can no longer visit government offices to handle various administrative needs. This paper aims to discuss the shortcomings and advantages of developing e-government in Indonesia and the factors that cause lag in the development of e-government development in Indonesia. This research uses functional method legal research using a comparative study conducted with the aim of reconstruction, namely showing a study and comparison of the e-government system from Denmark as a comparison country with Indonesia. The Indonesian government can see Denmark's success in achieving e-government, which is supported by collaboration between the government and the private sector; with this collaboration, the government can maximize public services to the community.